2018
DOI: 10.1093/ofid/ofy032
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Persistence of Plasma HIV-1 RNA During Long-term Continuously Suppressive Firstline Antiretroviral Therapy

Abstract: BackgroundPersistence of plasma HIV-1 RNA during seemingly effective antiretroviral thereapy (ART) is incompletely understood. Using an ultrasensitive assay, this cross-sectional study investigated residual plasma HIV-1 RNA in subjects maintained on firstline ART with continuous viral load suppression <50 copies/mL for ≤15 years without recognized viral load blips or treatment interruptions and explored its relationship with the duration of suppressive ART, efavirenz concentrations in plasma, 2-LTR circular HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…On the other hand, the impact of an early start to therapy on immunological recovery was debated by Amu et al, who showed that the expression of activation (HLA-DR and CD38 on CD4+ T cells) and terminal differentiation (CD127 on CD8+ T cells) markers in T cells were abnormal but comparable between early- and late-treated patients [68]. Similarly, Ruggiero et al demonstrated that there was no difference in levels of soluble and cellular markers of activation measured in patients that started ART at different times after diagnosis [69,70]. These characteristics, alongside early treatment, minimize HIV reservoir size and diversity, prevent the quantitative loss of Th17 cells, and positively impact on local and systemic T cell activation [71,72,73,74,75].…”
Section: Initiation and Duration Of Art Can Affect Chronic Immune mentioning
confidence: 99%
“…On the other hand, the impact of an early start to therapy on immunological recovery was debated by Amu et al, who showed that the expression of activation (HLA-DR and CD38 on CD4+ T cells) and terminal differentiation (CD127 on CD8+ T cells) markers in T cells were abnormal but comparable between early- and late-treated patients [68]. Similarly, Ruggiero et al demonstrated that there was no difference in levels of soluble and cellular markers of activation measured in patients that started ART at different times after diagnosis [69,70]. These characteristics, alongside early treatment, minimize HIV reservoir size and diversity, prevent the quantitative loss of Th17 cells, and positively impact on local and systemic T cell activation [71,72,73,74,75].…”
Section: Initiation and Duration Of Art Can Affect Chronic Immune mentioning
confidence: 99%
“…All subjects received first-line ART regimen according to Chinese guidelines for diagnosis and treatment of HIV/AIDS [26]. This included two nucleoside reverse transcriptase inhibitors (NRTIs) and a non-nucleoside reverse transcriptase inhibitor (NNRTI) that are widely used globally [27][28][29][30][31]. All participants were followed up every 3 to 6 months for evaluation of VL, CD4 + T cell counts, and other routine clinical parameters.…”
Section: Study Populationmentioning
confidence: 99%
“… 21 , 22 Notably, much of the HIV DNA is defective and cannot support the production of replication-competent virions, but it can support the production of viral proteins. 23 , 24 The amount of cell-associated DNA and RNA in blood has been associated with levels of T-cell activation, T-cell proliferation, and soluble markers of inflammation in many 25 , 26 , 27 , 28 , 29 but not all 30 studies.…”
Section: Introductionmentioning
confidence: 99%